Acute Toxicity and Hepatotoxicity Evaluation of Methanol Extract of Root Bark of Calotropis gigantea in Rats - Hasballah, Kartini; Sarong, Murniana; Rusly, Renzavaldy; Tantri, Karina; Mulia, Vera Dewi (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Many studies of root extract of Calotropis gigantea have been done to prove its potential as anticancer, antimicrobial, etc. agent C. gigantea plant itself is very easy to grow in tropical countries. However, studies of acute toxicity of C. gigantea root extract has not been performed.The purpose of this research was to know the safety level, the chemical constituents, and the acute toxicity of methanol extract of C. gigantea root bark given orally on Rattus norvegicus in rats. C. gigantea root bark was extracted by using methanol. The methanol extract was suspended in 1% sodium carboxymethyl cellulose (CMC) and administered orally by gavage (1250, 2500 and 5000 mg/kg) in separate groups. On the day of fifteen, all animals were anesthetized and some selected vital organs were excised, weighed and macroscopically examined. The liver was assessed histopathologically. There were no lethal effects, behavioral changes and no significant change in body and organ weights compared to control after the administration of the extracts. Thus, the value of LD50 for oral administration of methanol extracts from root bark of C. gigantea was larger than 5000 mg/kg. Methanol extract of C. gigantea root bark must be considered safe enough as none of the rats were died along the study. But, it can damage the hepatic cell, if given in higher dose. Dhaka Univ. J. Pharm. Sci. 17(2): 243-250, 2018 (December)